Fighting "low equilibria" by doubling the minimum wage? : Hungary's experiment - Gábor Kertesi; János Köllîo (Institute for the Study of Labor (IZA), 2003)
In January 2001 the Hungarian government increased the minimum wage from Ft 25,500 to Ft 40,000. One year later the wage floor rose further to Ft 50,000. The paper looks at the short-run impact of the first hike on small-firm employment and flows between employment and unemployment. It finds that the hike significantly increased labor costs and reduced employment in the small firm sector; and adversely affected the job retention and job finding probabilities of low-wage workers. While the conditions for a positive employment effect were mostly met in depressed regions spatial inequalities were amplified rather than reduced.
Keywords: P23; J38; R23; 330; minimum wages; transition; regional labor markets; Mindestlohn; Beschäftigungseffekt; Klein- und Mittelunternehmen; Regionaler Arbeitsmarkt; Regionale Disparität; Ungelernte Arbeitskräfte; Schätzung; Ungarn